2022
DOI: 10.1039/d1ra09025a
|View full text |Cite
|
Sign up to set email alerts
|

Polar/apolar interfaces modulate the conformational behavior of cyclic peptides with impact on their passive membrane permeability

Abstract: This study uses molecular dynamics and Markov state models to analyse how interfaces interact with cyclic decapeptides and modulate their dynamic and equilibrium properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 67 publications
4
36
0
Order By: Relevance
“…Molecular dynamics simulations by the Akiyama group showed that cyclic peptides with low or moderate lipophilicity tend to interact favorably at the head-group region of the membrane, where their polar groups have contact with the aqueous layer and the polar head groups, while their hydrophobic regions are solvated by the lipid tails . The Riniker group, also using molecular dynamics, reported that the formation of a contiguous hydrophobic surface patch was important for the passive membrane permeation of certain cyclic decapeptides . Our work shows that this principle is also important for the permeability of nonpeptidic macrocycles and indeed that, at least for the compounds in our set, the degree of spatial bias between polar and nonpolar regions of the molecule in the most stable low dielectric conformation is a major determinant of passive permeability.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Molecular dynamics simulations by the Akiyama group showed that cyclic peptides with low or moderate lipophilicity tend to interact favorably at the head-group region of the membrane, where their polar groups have contact with the aqueous layer and the polar head groups, while their hydrophobic regions are solvated by the lipid tails . The Riniker group, also using molecular dynamics, reported that the formation of a contiguous hydrophobic surface patch was important for the passive membrane permeation of certain cyclic decapeptides . Our work shows that this principle is also important for the permeability of nonpeptidic macrocycles and indeed that, at least for the compounds in our set, the degree of spatial bias between polar and nonpolar regions of the molecule in the most stable low dielectric conformation is a major determinant of passive permeability.…”
Section: Discussionmentioning
confidence: 62%
“…It is a well-established hypothesis that the membrane permeability of macrocycles can be enhanced for MCs that can undergo a so-called “chameleonic” conformational changethat is when, in a low dielectric environment, the molecule can adopt an alternative conformation that buries polar features. ,, The results described above establish that many of the MCs in our set can access multiple conformations in solution and that consideration of certain physicochemical properties that depend on the conformation is necessary to accurately model permeability. We therefore evaluated the extent to which chameleonic conformational change might contribute to permeability among our compounds.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations